Profile and Motivation of Entrepreneur Women in North Borneo, Indonesia - Lee, Cheng-Wen; Hidayat, Nurul (Metris: Jurnal Sains dan Teknologi, 2017)
This study aimed to describe the profile of entrepreneurship and motivation of female entrepreneurs and employees in North Borneo. The study of the behavior of entrepreneurs was developed in different perspectives: the economic perspective, the perspective of psychology, and sociology perspective. This study used primary data obtained using the survey method. A number of 300 questionnaires was distributed (with the response rate of 95%) in North Borneo. The questionnaires were distributed in five regions i.e. Tarakan city, Bulungan district, Malinau district, Tana Tidung district and Nunukan district. In this study, the Manifest Needs Questionnaire (MNQ) developed by Indarti and Wulandaru (2003) was used. This instrument was used to measure four respondents needs: the need for achievement, need for affiliation, need for autonomy and the need for domination. Based on statistical analysis, this research proved that women entrepreneurs were more motivated by the need for a higher performance than the female employees in North Borneo. In term of the need for affiliation, no evidence that women entrepreneur was more motivated than female employee. The results also showed that women entrepreneurs were more motivated by the need for higher autonomy than female employees as well as for the need for higher predominance.